Interactions between fungi of standard paint test method BS3900. (October 2015) - Gaylarde, Christine; Otlewska, Anna; Celikkol-Aydin, Sukriye; Skóra, Justyna; Sulyok, Michael; Pielech-Przybylska, Katarzyna; Gillatt, John; Beech, Iwona; Gutarowska, Beata
Abstract: Fungi are the principal deteriorating microflora on painted surfaces and standard test BS3900 uses a mixed fungal inoculum to assess anti-fungal agents in paint films. At the end of such a test with non-biocide containing (control) paint, Ulocladium atrum was shown by FESEM, culture and DGGE analysis to be the major surviving colonizer. Penicillium purpurogenum was also significant according to FESEM and culture results, and digital microscopy showed paint degrading activity. Laboratory studies on lab media showed that U. atrum had little antagonistic action against the other isolates used in the test, although it was one of the fastest growing fungi on malt extract agar. P. purpurogenum inhibited 10 of the other fungal isolates. Secondary metabolites, which could be involved in fungal antagonistic activity, were detected in all but two of the filamentous fungi and none of the three yeasts used in the inoculum. U. atrum produced the anti-fungal compound known as Antibiotic PF 1052. Although the three yeasts seemed to participate little in the final biofilm, they could be important in biocide assessment. Highlights: Interaction between fungi of test BS3900 studied on lab media and painted gypsum panels. Digital microscopy, FESEM, EDX, DGGE, growth, ergosterol and extrolite analyses used. Ulocladium atrum principal coloniser on paint after 12 weeks. Penicillium purpurogenum also significant survivor and major antagonist on lab medium. Extrolites identified in all but 5 of 14 isolates and anti-fungal PF 1052 in U. atrum.